Effective Methods in Teaching Grammar - Khamidova Nilufar (Research Parks Publishing LLC, 2021)
English grammar is notoriously difficult to learn for both native and second-language speakers. There are so many intricacies, obscure rules, and exceptions that it comes as no surprise that different generation of teachers have used various approaches to teaching grammar to train literate English writers. In the past, memorizationbased techniques that relied on repetition slowly gave way to more creative methods